2018
DOI: 10.5380/ce.v23i1.54280
|View full text |Cite
|
Sign up to set email alerts
|

Características Do Comportamento Suicida De Homens E Mulheres Em Tratamento Psiquiátrico

Abstract: RESUMO: Objetivo: identificar características do comportamento suicida e fatores de risco de homens e mulheres com transtornos psiquiátricos. Método: estudo quantitativo de 410 prontuários de pacientes psiquiátricos em tratamento, de 1997 a 2014, com análise descritiva e inferencial dos prontuários do serviço, no período de abril a dezembro de 2015, em um Centro de Atenção Psicossocial de Divinópolis/Minas Gerais. Resultado: uma maior frequência do comportamento suicida entre as mulheres foi, também, o motivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
5
0
7
Order By: Relevance
“…A study carried out in a CAPSIII identified a prevalence of suicidal behavior of 38.7% for women and 31.8% for men; greater suicidal ideation among women (28.1%) and greater suicide attempt among men (23.7%) (12) . Among health students, the prevalence of ideation is 22% and higher among men (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out in a CAPSIII identified a prevalence of suicidal behavior of 38.7% for women and 31.8% for men; greater suicidal ideation among women (28.1%) and greater suicide attempt among men (23.7%) (12) . Among health students, the prevalence of ideation is 22% and higher among men (13) .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study carried out with 253 patients in Alagoas (12) observed that the presence of current depression increases the risk of suicide by more than six times, compared to those who do not have this disorder, with this risk being moderate to severe among nephropaths/cardiopaths. The presence of Generalized Anxiety Disorder has been shown to be associated with a risk of suicide four times greater than that of the population without the disorder, tending to be of mild severity among the nephropaths/cardiopaths investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of psychological disorder appears as an important vulnerabilizing aspect for suicide (33) . It is assumed that 90% of people who commit suicide have disorders of this sort (34) . However, depression occupies a prominent position, being considered the most common disorder in individuals who die by suicide (35) .…”
Section: -Proximal Social Determinants Of Healthmentioning
confidence: 99%
“…A study conducted with 410 patients from a Psychosocial Care Center in Minas Gerais observed a statistically significant association between suicidal behavior and psychiatric comorbidity (psychotic or delusional disorders and maniac episode or bipolar affective disorder) among women. Men, in turn, presented a significant relationship between depression and psychiatric comorbidity (depression, schizophrenia, or disorders due to illicit drug use) and suicide (34) .…”
Section: -Proximal Social Determinants Of Healthmentioning
confidence: 99%
“…Devido a sua multifatoriedade, o comportamento suicida pode estar ligado a fatores biológicos e psicológicos associados ao contexto socioeconômico (MARÍN-LEÓN; OLIVEIRA; BOTEGA, 2012; GONÇALVES et al, 2014). Dentre estes fatores, destacam-se os transtornos mentais os quais estão presentes em mais de 90% daqueles que cometem suicídio, sendo observada uma alta frequência de casos de suicídio ou tentativa entre os portadores de TAB (NERY-FERNANDES; MIRANDA-SCIPPA, 2013; BOTEGA, 2014; APA, 2014; RUNESON et al, 2016).Mundialmente, os homens apresentam os maiores índices de suicídio, porém o maior número de tentativas é observado no gênero feminino, possivelmente, devido ao fato de os homens, geralmente, serem mais impulsivos e utilizarem métodos mais letais durante a tentativa de suicídio (CABRAL;PENDLOSKI, 2016;BOTTI et al, 2018).Estudos realizados no Brasil confirmam essa tendência, sendo apontados à ocorrência de suicídios entre homens em uma proporção de 3:1, quando comparados às mulheres, relação que se modifica quanto às tentativas de suicídio, em que se evidenciam a maior proporção entre as mulheres com taxa de três vezes maior do que os homens (NERY-FERNANDES;MIRANDA-SCIPPA, 2013).Entre pessoas com TAB, o risco de suicídio é muito mais elevado quando comparados coma população geral e entre aqueles que possuem outros transtornos psiquiátricos, deste modo se faz necessária à compreensão desses fatores para a prevenção do suicídio(NERY- FERNANDES, 2013;DUARTE et al, 2015;BOTTI et al, 2018).…”
unclassified